A study protocol to explore the effectiveness and implementation of mobile community outreach services for women who use drugs in Baltimore, Maryland: The SHOUT Study - Sewika Sulpe; Catherine Tomko; Emily Clouse; Andrea L. Wirtz; Brian Weir; Nouran El-Ashry; Susan G. Sherman (PLoS ONE, 2025)
The opioid overdose crisis has continued to affect women who use drugs (WWUD), particularly in urban cities such as Baltimore, Maryland, where fatal overdose rates rank among the highest in the nation. Despite evidence demonstrating the impact of mobile health services in serving underserved populations, few interventions are specifically tailored to meet the unique needs of WWUD. The Sustained Harm Reduction OUTreach (SHOUT) study evaluates the effectiveness and implementation of a harm reduction–based mobile outreach service operated by a community-based organization serving WWUD in Southwest Baltimore. The “intervention group” consists of WWUD recruited within the organization’s catchment area, while the “control group” comprises those recruited from neighborhoods outside of the organization’s catchment area. The study’s three aims are: (1) to conduct in-depth interviews with WWUD (N=12) to assess the feasibility of using a modified respondent-driven sampling (RDS) method; (2) to conduct a prospective cohort study comparing intervention (N=250) and control (N=150) groups over 18 months to assess nonfatal overdose and healthcare access outcomes; and (3) to evaluate intervention implementation using the RE-AIM framework. The study is guided by Andersen’s Behavioral Model for Vulnerable Populations and Rhodes’s Risk Environment Framework. Preliminary findings suggest that a modified RDS approach is both feasible and acceptable among WWUD. Aim 2 will examine the effect of mobile services on reducing nonfatal overdoses by promoting harm reduction practices within participants’ social and physical environments. Aim 3 will incorporate qualitative and cost-effectiveness analyses to contextualize the program’s impact and sustainability. This study addresses critical service gaps for WWUD by integrating and providing low-barrier harm reduction services offered on an accessible mobile van. Findings will inform scalable, community-driven strategies to reduce overdose mortality and improve health equity among structurally vulnerable populations. Strengths, limitations, and plans for results dissemination are discussed.